Electrolyte for lithium battery and lithium titanate battery

CN112635828BActive Publication Date: 2026-10-30GREE ALTAIRNANO NEW ENERGY INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202011483155.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2026-10-30
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种锂电池用电解液及钛酸锂电池,以解决现有技术中的钛酸锂负极高温容易胀气的问题

Benefits of technology

[0018]应用本发明的技术方案,通过向电解液中添加热敏传感有机化合物,该热敏有机化合物溶于有机溶剂,且在温度升高达到一定阈值时,会在电极表面形成一层薄膜,并且其电阻突然增大2~5个数量级,使得电极表面瞬间变成绝缘体,阻止电子的通过,防止电池内部的活性物质结构继续发生不可逆变化,并且防止电解液的继续分解,进而阻止了电池继续产生气体和热量,可有效降低电池胀气、起火或爆炸的风险。在温度重新降低到阈值以下,该热敏传感有机化合物重新溶解回到有机溶剂中,电池可以重新恢复充、放电功能。有机化合物的量需要控制在一定的范围内,超出此范围,会影响电池常温下的放电效果。低于此范围,则无法在温度超过温度阈值时快速、有效阻断电子通过,进而无法防止电池继续产生气体和热量。综上所述,本申请的电解液通过添加可溶解于有机溶剂的热敏化合物,有效降低了电池胀气、起火或爆炸的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112635828B_ABST
    Figure CN112635828B_ABST
Patent Text Reader

Abstract

The application provides a lithium battery electrolyte and a lithium titanate battery. The lithium battery electrolyte comprises a lithium salt, an organic solvent and an additive, the additive comprises a heat-sensitive organic compound, and the weight percentage of the heat-sensitive organic compound in the total amount of the organic solvent and the additive is 1-10%. By adding the heat-sensitive organic compound to the electrolyte, the heat-sensitive organic compound is dissolved in the organic solvent, and when the temperature increases to a certain threshold value, a thin film is formed on the electrode surface, and the resistance of the thin film suddenly increases by 2-5 orders of magnitude, so that the electrode surface becomes an insulator instantaneously, prevents the through of electrons, prevents the irreversible change of the active material structure in the battery, prevents the continuous decomposition of the electrolyte, and further prevents the continuous generation of gas and heat in the battery, so that the risk of battery swelling, fire or explosion can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery materials technology, and more specifically, to an electrolyte for lithium batteries and a lithium titanate battery. Background Technology

[0002] Currently, most commercially available lithium-ion battery anode materials are lithium-intercalated carbon materials. Because the potential of the carbon electrode after lithium intercalation is very close to that of metallic lithium, metallic lithium easily deposits on the carbon electrode surface during battery use. This lithium reacts with the electrolyte to produce a flammable gas mixture, thus limiting the safety of lithium-ion materials in power batteries. Furthermore, during Li intercalation or deintercalation, carbon materials with a 2D layered structure undergo shrinkage changes, with a volume change rate of approximately 10%, severely affecting the battery's cycle stability. Therefore, it is necessary to find new anode materials that are safer and more reliable than carbon anodes.

[0003] Lithium titanate (Li4Ti5O3) is a low-potential transition metal oxide and composite oxide. 12 The negative electrode material, Li4Ti5O, has attracted widespread attention. 12 With a lithium electrode potential of 1.55V, the theoretical specific capacity is 175mAh / g, and the actual specific capacity is 150-160mAh / g. During Li insertion and extraction, the volume change of the 3D spinel structure is less than 1%, hence it is called a "zero-strain material." This avoids structural damage caused by the repeated insertion and extraction of lithium ions during charge-discharge cycles, thus improving battery life. 12 It exhibits superior cycle performance compared to carbon anodes. Meanwhile, at 25°C, Li₄Ti₅O₂... 12 The chemical diffusion coefficient is 2 × 10⁻⁶. -8 cm 2 The diffusion coefficient of Li4Ti5O is an order of magnitude larger than that of carbon anode materials, allowing for rapid and multi-cycle charge-discharge operation. 12 Its particle size is in the nanometer range, which determines its wide temperature tolerance.

[0004] However, in practical applications, it has been found that batteries with lithium titanate as the negative electrode are prone to gas expansion at high temperatures. When the battery is subjected to abuse conditions (such as squeezing, collision, high temperature, overcharging and discharging, short circuit, etc.), it is prone to fire and explosion, which has made people increasingly concerned about the safety of electric vehicles, especially lithium-ion batteries. Summary of the Invention

[0005] The main objective of this invention is to provide an electrolyte for lithium batteries and a lithium titanate battery to solve the problem of easy gas expansion at high temperatures in the lithium titanate negative electrode in the prior art.

[0006] To achieve the above objectives, according to one aspect of the present invention, an electrolyte for lithium batteries is provided, comprising a lithium salt, an organic solvent, and an additive, wherein the additive comprises a thermosensitive organic compound, and the thermosensitive organic compound comprises 1 to 10% by weight based on the total amount of the organic solvent and the additive.

[0007] Furthermore, the aforementioned thermosensitive organic compound is selected from one or more of the following: p-toluenebenzyl oxalate diester, N-alkyl-substituted acrylamide polymer, N,N-di-n-pentyl-m-aminophenol, and N-vinylformamide copolymer with styrene.

[0008] Furthermore, the above-mentioned additives also include silane-containing carbonates, preferably with a weight percentage of 1 to 10% based on the total amount of organic solvents and additives.

[0009] Preferred carbonates containing silane groups have the following general structural formula:

[0010] R1 to R4 are each independently selected from any one of alkyl groups having 1 to 4 carbon atoms. Preferably, R1, R2, R3, and R4 are all the same alkyl group. R5 is -OCH3 or -OC2H5. R6 is an ethylene carbonate residue, propylene carbonate residue, dimethyl carbonate residue, diethyl carbonate residue, or methyl ethyl carbonate residue. n and m are each independently any integer from 1 to 5.

[0011] Furthermore, R6 above is an ethylene carbonate residue or a propylene carbonate residue.

[0012] Furthermore, based on the total amount of organic solvents and additives, the weight percentage of the organic solvents is 80-98%, preferably 1-4% of the weight percentage of the thermosensitive organic compound, more preferably 2.5-3.5%, the weight percentage of the silane-containing carbonate is 1-4%, and the weight percentage of the organic solvents is 92-98%.

[0013] Furthermore, the organic solvents mentioned above are selected from any one or more of carbonate solvents and sulfonate solvents; the carbonate solvents are selected from one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and the sulfonate solvents are selected from one or more of 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, propenyl 1,3-propanesulfonate lactone, and ethyl methanesulfonate.

[0014] Further, the aforementioned organic solvents include ethylene carbonate, vinylene carbonate, methyl ethyl carbonate, diethyl carbonate, and 1,3-propanesulfonate lactone; preferably, based on the total amount of organic solvents and additives, the weight percentage of ethylene carbonate is 18%–30%, the weight percentage of methyl ethyl carbonate is 25%–35%, the weight percentage of diethyl carbonate is 20%–30%, the weight percentage of 1,3-propanesulfonate lactone is 10%–15%, and the weight percentage of vinylene carbonate is 1%–5%.

[0015] Furthermore, the lithium salt mentioned above is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl)imide.

[0016] Furthermore, the concentration of lithium salt in the electrolyte for the above-mentioned lithium battery is 0.7–1.5 mol / L.

[0017] According to another aspect of the present invention, a lithium titanate battery is provided, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is any of the above-mentioned lithium battery electrolytes.

[0018] By applying the technical solution of this invention, a thermosensitive organic compound is added to the electrolyte. This thermosensitive organic compound is soluble in organic solvents, and when the temperature rises to a certain threshold, it forms a thin film on the electrode surface, with its resistance suddenly increasing by 2 to 5 orders of magnitude. This instantly turns the electrode surface into an insulator, preventing the passage of electrons, preventing irreversible changes in the structure of the active materials inside the battery, and preventing further decomposition of the electrolyte. This, in turn, prevents the battery from continuing to generate gas and heat, effectively reducing the risk of battery swelling, fire, or explosion. When the temperature drops back below the threshold, the thermosensitive organic compound redissolves back into the organic solvent, and the battery can resume its charging and discharging functions. The amount of organic compound needs to be controlled within a certain range; exceeding this range will affect the battery's discharge performance at room temperature. Below this range, it cannot quickly and effectively block the passage of electrons when the temperature exceeds the temperature threshold, thus failing to prevent the battery from continuing to generate gas and heat. In summary, the electrolyte of this application, by adding a thermosensitive compound soluble in organic solvents, effectively reduces the risk of battery swelling, fire, or explosion. Attached Figure Description

[0019] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0020] Figure 1 The graphs showing the internal resistance of Embodiment 1, Embodiment 2 and Comparative Example 1 at different temperatures are illustrated.

[0021] Figure 2The overcharge test curves of Embodiment 1, Embodiment 2 and Comparative Example 1 of the present invention are shown;

[0022] Figure 3 The overcharge test temperature curves of Embodiment 1, Embodiment 2 and Comparative Example 1 of the present invention are shown;

[0023] Figure 4 A comparison diagram of battery thickness in Embodiment 1, Embodiment 2, and Comparative Example 1 of the present invention is shown; and

[0024] Figure 5 The battery room temperature cycling curves of Embodiment 1, Embodiment 2 and Comparative Example 1 of the present invention are shown. Detailed Implementation

[0025] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0026] As described in the background section of this application, lithium batteries using lithium titanate as the negative electrode are prone to gas expansion at high temperatures. When the battery is subjected to abuse conditions (such as compression, impact, high temperature, overcharge and discharge, short circuit, etc.), it is prone to fire and explosion. To solve the above problems, this application provides an electrolyte for lithium batteries and a lithium titanate battery.

[0027] In a typical embodiment of this application, an electrolyte for lithium batteries is provided, comprising lithium salt, organic solvent, and additives, the additives including a thermosensitive organic compound, wherein the weight percentage of the thermosensitive organic compound is 1% to 10% based on the total amount of organic solvent and additives.

[0028] This application introduces a thermosensitive organic compound into the electrolyte. This compound is soluble in organic solvents and, when the temperature rises to a certain threshold, forms a thin film on the electrode surface. The film's resistance suddenly increases by 2 to 5 orders of magnitude, instantly turning the electrode surface into an insulator. This prevents electrons from passing through, thus preventing irreversible changes in the structure of the active materials inside the battery and further decomposition of the electrolyte. Consequently, it prevents the battery from generating gas and heat, effectively reducing the risk of battery swelling, fire, or explosion. When the temperature drops back below the threshold, the thermosensitive organic compound redissolves back into the organic solvent, and the battery can resume its charging and discharging functions. The amount of the organic compound needs to be controlled within a certain range. Exceeding this range will affect the battery's discharge performance at room temperature. Below this range, it cannot quickly and effectively block electrons when the temperature exceeds the threshold, thus failing to prevent the battery from generating gas and heat. In summary, the electrolyte of this application, by adding a thermosensitive compound soluble in organic solvents, effectively reduces the risk of battery swelling, fire, or explosion.

[0029] The thermistor organic compound used in this application can be any compound that is soluble in commonly used organic solvents in electrolytes, can form a thin film on the electrode surface to prevent electrons from passing through after exceeding a temperature threshold, and can redissolve in the organic solvent after the temperature drops below the threshold. To form a thin film on the electrode surface more quickly and effectively to block electrons from passing through when the temperature reaches a level harmful to the battery, without affecting the room-temperature charge and discharge performance of the lithium battery, the thermistor organic compound is preferably selected from one or more of the following: p-toluenebenzyl oxalate diester, N-alkyl-substituted acrylamide polymer, N,N-di-n-pentyl-m-aminophenol, and N-vinylformamide copolymer with styrene.

[0030] In one embodiment of this application, the preferred additive further includes a silane-containing carbonate. By adding the aforementioned silane-containing carbonate, gases generated during the chemical reaction between the positive and negative electrodes during battery use can be effectively adsorbed, keeping the electrodes tightly bonded, reducing the loss of lithium ions embedded in the positive and negative electrodes, thereby maintaining high battery capacity and low expansion, and extending the lifespan of the lithium-ion battery. To further effectively adsorb the gases generated by the battery without affecting its normal charge and discharge function, the weight percentage of the silane-containing carbonate is preferably 1-10% based on the total amount of organic solvent and additives; more preferably, the silane-containing carbonate polymer has the following general structural formula:

[0031]

[0032] R1 to R4 are each independently selected from any one of alkyl groups having 1 to 4 carbon atoms. Preferably, R1, R2, R3, and R4 are all the same alkyl group. R5 is -OCH3 or -OC2H5. R6 is an ethylene carbonate residue, propylene carbonate residue, dimethyl carbonate residue, diethyl carbonate residue, or methyl ethyl carbonate residue. n and m are each independently any integer from 1 to 5.

[0033] During the formation of the electrolyte using a silane-containing carbonate polymer, this invention can create a Si-O-Si network structure on the negative electrode surface. This structure can suppress the damage to the SEI film on both the positive and negative electrode surfaces by the electrolyte under high temperature and pressure during subsequent charging and discharging. It also prevents the continuous deposition of lithium halides formed by the reaction of hydrogen halides with the electrolyte on the negative electrode surface, which would otherwise lead to SEI film thickening and reduced lithium-ion conductivity. Furthermore, during battery charging and discharging, the generated hydrogen halide gas undergoes a substitution reaction with R6 in the Si-O-Si network structure surrounding the negative electrode, generating a silane-containing carbonate halide polymer, as well as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, or methyl ethyl carbonate. This avoids the problem of battery performance degradation and shortened lifespan caused by the large amount of gas generated during battery operation leading to battery volume expansion. Moreover, this compound does not react with other substances in the electrolyte and will not affect the normal use of the battery.

[0034] To further enhance the gas adsorption effect of the aforementioned silane-based carbonates, R6 is preferably an ethylene carbonate residue or a propylene carbonate residue.

[0035] The electrolyte of this application contains a thermosensitive organic compound and a silane-containing carbonate polymer additive. These additives can effectively improve battery safety and extend battery life. Simultaneously, it is also necessary to further ensure the conductivity of the electrolyte. Preferably, based on the total amount of organic solvent and additives, the weight percentage of the organic solvent is 80-98%, more preferably 1%-4% (preferably 2.5-3.5%), the weight percentage of the silane-containing carbonate is 1-4%, and the weight percentage of the organic solvent is 92-98%, to further achieve a balance between the conductivity of the electrolyte and safety under abuse conditions.

[0036] The organic solvent used in this application can be selected from any organic solvent commonly used in electrolytes in the prior art. At the same time, in order to improve the solubility of the above-mentioned additives in organic solvents, prevent chemical reactions with the additives, and improve the high temperature resistance and high voltage resistance of the battery, the organic solvent is preferably selected from any one or more of carbonate solvents and sulfonate solvents. The carbonate solvent is selected from one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The sulfonate solvent is selected from one or more of 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, propylene-1,3-propanesulfonate lactone, and ethyl methanesulfonate.

[0037] To further enhance the high-temperature and high-voltage resistance of batteries and improve the solubility of additives, organic solvents are preferably composed of ethylene carbonate, vinylene carbonate, methyl ethyl carbonate, diethyl carbonate, and 1,3-propanesulfonate lactone. Vinylene carbonate can undergo free radical polymerization on the carbon anode surface to produce polyalkyl lithium carbonate compounds, thereby effectively suppressing solvent molecule co-intercalation reactions. Preferably, based on the total amount of organic solvent and additives, the weight percentages are as follows: ethylene carbonate 18%–30%, methyl ethyl carbonate 25%–35%, diethyl carbonate 20%–30%, 1,3-propanesulfonate lactone 10%–15%, and vinylene carbonate 1%–5%. By optimizing the above weight ratios, the aforementioned beneficial properties of the organic solvents are further enhanced.

[0038] The lithium salt used in this application can be any lithium salt commonly used in lithium-ion batteries in the prior art. In order to obtain a high-performance lithium-ion battery that works synergistically with the additives and solvents of this application, it is preferred that the lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(trifluoromethanesulfonyl)imide.

[0039] To further improve the charging and discharging function of lithium-ion batteries, it is preferable that the concentration of lithium salt in the electrolyte for lithium batteries is 0.7 to 1.5 mol / L.

[0040] In another typical embodiment of this application, a lithium titanate battery is provided, including a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is any of the above-mentioned lithium battery electrolytes.

[0041] Lithium batteries using the electrolyte described in this application can form a thin film on the electrode surface when the temperature rises to a certain threshold, increasing the resistance by 2 to 5 orders of magnitude. This instantly turns the electrode surface into an insulator, preventing the passage of electrons. The internal circuit of the battery is broken at this point, the current instantly becomes zero, and the voltage also becomes zero. The battery will not continue to heat up and undergo irreversible changes, effectively preventing combustion or explosion. Simultaneously, for electrolytes with additives including silane-based carbonates, the gases generated at the positive and negative electrodes are effectively absorbed, keeping the electrodes tightly bonded and reducing the loss of lithium ions embedded in the positive and negative electrodes. This maintains high battery capacity and low expansion, thereby extending the lifespan of the lithium-ion battery.

[0042] The beneficial effects of the present invention will be further illustrated below with reference to embodiments and comparative examples.

[0043] Preparation of electrolyte

[0044] Example 1

[0045] Based on the total weight of organic solvents and additives, the organic solvent content is 93% (a mixture of five organic solvents: 18.5% ethylene carbonate, 34.2% methyl ethyl carbonate, 25.4% diethyl carbonate, 13.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 7% (3.5% dimethylbenzyl oxalate and 3.5% silane-containing carbonate polymer). The silane-containing carbonate polymer is...

[0046] R1, R2, R3 and R4 are all methyl alkyl groups, R5 is -OCH3, R6 is an ethylene carbonate residue, n=1, m=1.

[0047] Example 2

[0048] Based on the total weight of organic solvents and additives, the organic solvent content is 95% (a mixture of five organic solvents: 19.5% ethylene carbonate, 35.2% methyl ethyl carbonate, 25.4% diethyl carbonate, 13.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 5% (2.5% dimethylbenzyl oxalate and 2.5% silane-containing carbonate polymer). The silane-containing carbonate polymer is...

[0049] R1, R2, R3 and R4 are all ethane groups, R5 is -OCH3, R6 is a propylene carbonate residue, n=2, m=2.

[0050] Example 3

[0051] Based on the total weight of organic solvents and additives, the content of organic solvents is 95% (a mixture of five organic solvents: 19.5% ethylene carbonate, 35.2% methyl ethyl carbonate, 25.4% diethyl carbonate, 13.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the content of lithium hexafluorophosphate is 1.1 mol / L; and the content of additives is 5% (5% dimethyl benzyl oxalate).

[0052] Example 4

[0053] The difference from Example 3 is that,

[0054] The organic solvent content is 92% (a mixture of five organic solvents: 23.5% ethylene carbonate, 35.2% methyl ethyl carbonate, 20.4% diethyl carbonate, 11.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 8% (1% dimethyl benzyl oxalate, 3.5% propylene carbonate, and 3.5% vinylene carbonate).

[0055] Example 5

[0056] The difference from Example 3 is that,

[0057] The organic solvent content is 90% (a mixture of five organic solvents: 19.5% ethylene carbonate, 30.2% methyl ethyl carbonate, 25.4% diethyl carbonate, 13.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 10% (10% dimethyl benzyl oxalate).

[0058] Example 6

[0059] The difference from Example 1 is that,

[0060] The organic solvent content is 91% (a mixture of five organic solvents: 20.0% ethylene carbonate, 27.0% methyl ethyl carbonate, 28.0% diethyl carbonate, 15.0% 1,3-propanesulfonate lactone, and 1.0% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 9% (1% dimethyl benzyl alcohol oxalate, 1% silane-containing carbonate polymer, 3.5% propylene carbonate, and 3.5% vinylene carbonate).

[0061] Example 7

[0062] The difference from Example 1 is that,

[0063] The organic solvent content is 80.0% (a mixture of five organic solvents: 18.0% ethylene carbonate, 25.0% methyl ethyl carbonate, 20.0% diethyl carbonate, 12.0% 1,3-propanesulfonate lactone, and 5% vinylene carbonate); the lithium hexafluorophosphate content is 1.1 mol / L; and the additive content is 20% (10% dimethyl benzyl oxalate and 10% silane-containing carbonate polymer).

[0064] Example 8

[0065] The difference from Example 1 is that,

[0066] In silane-containing carbonate polymers, R1 is n-propyl, R2 is methyl, R3 is n-butyl, R4 is ethyl, R5 is -OC2H5, and R6 is a dimethyl carbonate residue, n=1, m=1.

[0067] Example 9

[0068] The difference from Example 8 is that n = 5 and m = 5.

[0069] Example 10

[0070] The difference from Example 1 is that the methylbenzyl alcohol oxalate diester is replaced with an N-alkyl-substituted acrylamide polymer.

[0071] Example 11

[0072] The difference from Example 1 is that methylbenzyl alcohol oxalate diester is replaced with N,N-di-n-pentyl-m-aminophenol.

[0073] Example 12

[0074] The difference from Example 1 is that methylbenzyl alcohol oxalate diester is replaced with N-vinylformamide and styrene copolymer.

[0075] Example 13

[0076] The difference from Example 1 is that 1,3-propanesulfonate lactone is replaced with ethyl methanesulfonate.

[0077] Example 14

[0078] The difference from Example 1 is that lithium hexafluorophosphate is replaced with lithium bis(trifluoromethanesulfonylimide).

[0079] Example 15

[0080] The difference from Example 1 is that the concentration of lithium hexafluorophosphate is 0.7 mol / L.

[0081] Example 16

[0082] The difference from Example 1 is that the concentration of lithium hexafluorophosphate is 1.5 mol / L.

[0083] Comparative Example 1

[0084] Based on the total weight of organic solvents and additives, the content of organic solvents is 93% (a mixture of five organic solvents: 18.5% ethylene carbonate, 34.2% methyl ethyl carbonate, 25.4% diethyl carbonate, 13.3% 1,3-propanesulfonate lactone, and 1.6% vinylene carbonate); the content of lithium hexafluorophosphate is 1.1 mol / L; and the content of additives is 7% (propylene carbonate (which can form an effective SEI film on the negative electrode surface) 3.5% and vinylene carbonate (which undergoes free radical polymerization on the carbon negative electrode surface to produce polyalkyl lithium carbonate compounds, thereby effectively inhibiting solvent molecule co-intercalation reaction) 3.5%).

[0085] Battery testing

[0086] Cell manufacturing

[0087] The ternary cathode material of lithium nickel cobalt manganese oxide and the anode material of lithium titanate, along with their conductive agents and binders, are stirred until uniform according to the mixing process requirements to prepare positive and negative electrode slurries. These slurries are then coated onto the positive and negative current collectors, respectively. The cells are then subjected to drying, rolling, slitting, stamping, and stacking processes. They are then encapsulated with aluminum-plastic film. The encapsulated cells are vacuum-baked and then injected with the electrolyte. After formation, aging, and capacity testing, a soft-pack battery is obtained.

[0088] The pouch batteries prepared in Examples 1 and 1 Comparative Example 1 were placed in an oven to test the change in internal resistance at different temperatures, as well as to test battery thickness and perform electrical performance tests such as rate capability, low temperature, and cycle life. Simultaneously, the batteries underwent safety performance tests according to the national standard GB18384-2020, including short-circuit tests, compression tests, heating tests, drop tests, temperature cycle tests, overcharge tests (including charging to 1.5 times the maximum charging voltage required by the national standard GB 18384-2020 and charging to 4.6V as required by the customer), over-discharge tests, and seawater immersion tests. The test results of Examples 1 and 1 Comparative Example 1 are as follows: Figures 1-5 As shown.

[0089] from Figure 1 It can be seen that when the temperature exceeds 120°C, the internal resistance of the battery in Example 1 is significantly higher than that of the battery in Comparative Example 1. When the temperature reaches 140°C, the pores in the separator inside the battery in Comparative Example 1 close, and the internal resistance gradually decreases. However, the internal resistance of the battery in Example 1 suddenly increases several times. That is, when the temperature reaches above 130°C, the electrolyte containing methylbenzyl alcohol oxalate can form a thin film on the electrode surface, and its resistance suddenly increases by several orders of magnitude, making the electrode surface instantly become an insulator.

[0090] Since the soft-pack battery corresponding to Example 1 passed all safety tests, while the battery in Comparative Example 1 only failed the overcharge test, the specific role of this invention during the overcharge test is analyzed in detail. During the test, the changes in battery voltage, current, and temperature are recorded. Figure 2 and Figure 3It can be seen that within the normal charge / discharge voltage range of the battery, charging with a 1C (75Ah) current raises the voltage to 4.6V. During this process, a small amount of the input energy is converted into heat, while most of the energy is stored in the form of chemical energy. When the battery voltage rises from 4.6V to 4.8V, most of the input energy is directly converted into heat, and the output heat energy increases, even exceeding the input electrical energy. An exothermic reaction occurs within this range. Subtracting the input electrical energy from the output heat energy, some chemical energy is released. This process involves a strong exothermic reaction, at which point the temperature reaches 140℃. Continuing to charge, for battery 1, all the input electrical energy is converted into heat energy, causing a rapid increase in the internal temperature of the battery. When the temperature is high enough (exceeding 300℃), a chemical reaction occurs at the anode, releasing even more heat, ultimately leading to thermal runaway and causing the battery to catch fire. For the soft-pack battery corresponding to Example 1, when the temperature reaches 140°C, the electrolyte containing methylbenzyl alcohol oxalate can form a thin film on the electrode surface, and its resistance suddenly increases by several orders of magnitude, making the electrode surface an insulator instantly, preventing the passage of electrons. At this time, the battery becomes an open circuit, and the current and voltage instantly become 0. Therefore, no energy is generated inside, allowing the battery to pass the test.

[0091] from Figure 4 and Figure 5 It can be seen that the average thickness of the battery corresponding to Example 1 is 18.09 mm, and the average thickness of the battery corresponding to Comparative Example 1 is 18.23 mm. The retention rate of the battery corresponding to Example 1 in 4C charge-discharge cycle is also higher than that of Comparative Example 1. This indicates that the additive can eliminate the gas generated during the chemical reaction, make the electrode sheets fit tightly, and reduce the loss of lithium ions embedded in the positive and negative electrodes. Therefore, it can maintain the high capacity and low expansion of the battery, thereby extending the service life of the lithium-ion battery.

[0092] The resistance at 140°C and the capacity retention after 3000 cycles of the batteries prepared in the above examples and comparative examples are recorded in Table 1.

[0093] Table 1

[0094]

[0095]

[0096] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0097] This application introduces a thermosensitive organic compound into the electrolyte. This compound is soluble in organic solvents and, when the temperature rises to a certain threshold, forms a thin film on the electrode surface. The film's resistance suddenly increases by 2 to 5 orders of magnitude, instantly turning the electrode surface into an insulator. This prevents electrons from passing through, thus preventing irreversible changes in the structure of the active materials inside the battery and further decomposition of the electrolyte. Consequently, it prevents the battery from generating gas and heat, effectively reducing the risk of battery swelling, fire, or explosion. When the temperature drops back below the threshold, the thermosensitive organic compound redissolves back into the organic solvent, and the battery can resume its charging and discharging functions. The amount of the organic compound needs to be controlled within a certain range. Exceeding this range will affect the battery's discharge performance at room temperature. Below this range, it cannot quickly and effectively block electrons when the temperature exceeds the threshold, thus failing to prevent the battery from generating gas and heat. In summary, the electrolyte of this application, by adding a thermosensitive compound soluble in organic solvents, effectively reduces the risk of battery swelling, fire, or explosion.

[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An electrolyte for lithium batteries, comprising lithium salt, organic solvent, and additives, characterized in that, The additive comprises a thermosensitive organic compound and a silane-containing carbonate, wherein the weight percentage of the thermosensitive organic compound and the weight percentage of the silane-containing carbonate are 1-10% based on the total amount of the organic solvent and the additive. The thermosensitive organic compound is selected from one or more of the following: p-methylbenzyl alcohol oxalate diester, N-alkyl-substituted acrylamide polymer, N,N-di-n-n-pentyl-m-aminophenol, and N-vinylformamide copolymer with styrene. The silane-containing carbonate has the following general structural formula: ; R1 to R4 are each independently selected from any one of alkyl groups having 1 to 4 carbon atoms, R5 is -OCH3 or -OC2H5, R6 is an ethylene carbonate residue, propylene carbonate residue, dimethyl carbonate residue, diethyl carbonate residue or methyl ethyl carbonate residue, and n and m are each independently any integer from 1 to 5.

2. The electrolyte for lithium batteries according to claim 1, characterized in that, R1, R2, R3, and R4 are all the same alkyl group.

3. The electrolyte for lithium batteries according to claim 1, characterized in that, R6 is a vinyl carbonate residue or a propylene carbonate residue.

4. The electrolyte for lithium batteries according to claim 1, characterized in that, The organic solvent has a weight percentage of 80-98% based on the total amount of the organic solvent and the additive.

5. The electrolyte for lithium batteries according to claim 4, characterized in that, Based on the total amount of the organic solvent and the additives, the weight percentage of the thermosensitive organic compound is 1-4%, the weight percentage of the silane-containing carbonate is 1-4%, and the weight percentage of the organic solvent is 92-98%.

6. The electrolyte for lithium batteries according to claim 5, characterized in that, The weight percentage of the heat-sensitive organic compound is 2.5-3.5% based on the total amount of the organic solvent and the additive.

7. The electrolyte for lithium batteries according to claim 1, characterized in that, The organic solvent is selected from any one or more of carbonate solvents and sulfonate solvents. The carbonate solvent is selected from one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The sulfonate solvent is selected from one or more of 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, and ethyl methanesulfonate.

8. The electrolyte for lithium batteries according to claim 7, characterized in that, The organic solvent includes ethylene carbonate, vinylene carbonate, methyl ethyl carbonate, diethyl carbonate, and 1,3-propanesulfonate lactone; based on the total amount of the organic solvent and the additives, the weight percentage of ethylene carbonate is 18%~30%, the weight percentage of methyl ethyl carbonate is 25%~35%, the weight percentage of diethyl carbonate is 20%~30%, the weight percentage of 1,3-propanesulfonate lactone is 10%~15%, and the weight percentage of vinylene carbonate is 1%~5%.

9. The electrolyte for lithium batteries according to claim 1, characterized in that, The lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium bis(trifluoromethanesulfonyl)imide.

10. The electrolyte for lithium batteries according to claim 1, characterized in that, The concentration of the lithium salt in the electrolyte for the lithium battery is 0.7~1.5 mol / L.

11. A lithium titanate battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The electrolyte is the lithium battery electrolyte according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • High-voltage lithium ion battery non-aqueous electrolyte and lithium ion battery containing electrolyte

    CN111129595A